Anti-inflammatory effect of pomegranate flower in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages - Jianjun Xu; Yongxin Zhao; Haji Akber Aisa (Taylor & Francis Group, 2017)
Context: Punica granatum L (Punicaceae) flower is an important diabetes treatment in oriental herbal medicine. Objective: This study investigates the inflammation effects of pomegranate flower (PFE) ethanol extract in LPS-induced RAW264.7 cells. Materials and methods: PFE (10, 25, 50, 100 μg/mL) was applied to 1 μg/mL LPS-induced RAW 264.7 macrophages in vitro. Levels of nitric oxide (NO), prostaglandin E2 (PGE2) and pro-inflammatory cytokines interleukin (IL)-1β (IL-1β), interleukin (IL)-6 (IL-6) and tumor necrosis factor (TNF-α) in the supernatant fraction were determined using enzyme-linked immunosorbent assay (ELISA). Expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS), phosphorylation of mitogen-activated protein kinase (MAPK) subgroups extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) and P38, as well as nuclear factor-κB (NF-κB) activation in extracts were detected via Western blot. Results: 10-100 μg/mL PFE decreased the production of NO (IC50 value = 31.8 μg/mL), PGE2 (IC50 value = 54.5 μg/mL), IL-6 (IC50 value = 48.7 μg/mL), IL-1β (IC50 value = 71.3 μg/mL) and TNF-α (IC50 value = 62.5 μg/mL) in LPS-stimulated RAW 264.7 cells significantly. A mechanism-based study showed that phosphorylation of ERK1/2, p38, JNK and translocation of the NF-B p65 subunit into nuclei were inhibited by the PFE treatment. Discussion and conclusion: These results show that PFE produced potential anti-inflammatory effect through modulating the synthesis of several mediators and cytokines involved in the inflammatory process.